2018
DOI: 10.14740/jocmr3467w
|View full text |Cite
|
Sign up to set email alerts
|

SGLT-2 Inhibitors and Cardiovascular Protection: Lessons and Gaps in Understanding the Current Outcome Trials and Possible Benefits of Combining SGLT-2 Inhibitors With GLP-1 Agonists

Abstract: Landmark trials on diabetes control have shown variable results in terms of cardiovascular benefits, with the majority showing a favorable effect of glycemic control on microvascular and, more recently, macrovascular complications. However, some trials pointed out a CV hazard with tight diabetes mellitus (DM) control. Most of those trials were assessing the impact of glycemic control, more than evaluating the effect of a certain medication. In the last decade, food and drugs administration (FDA) has mandated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 90 publications
0
11
0
Order By: Relevance
“…Previous trials can explain that there was no improvement in LVEF with SGLT2 inhibitors in our study. For HFrEF, changes in LVEF with SGLT2 inhibitors were more noticeable than with DPP4 inhibitors 13. NT-pro BNP level improved significantly in the SGLT2 inhibitor group, which affected cardiac function and ejection fraction, especially in the HFrEF group.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Previous trials can explain that there was no improvement in LVEF with SGLT2 inhibitors in our study. For HFrEF, changes in LVEF with SGLT2 inhibitors were more noticeable than with DPP4 inhibitors 13. NT-pro BNP level improved significantly in the SGLT2 inhibitor group, which affected cardiac function and ejection fraction, especially in the HFrEF group.…”
Section: Discussionmentioning
confidence: 91%
“…SGLT2 inhibitors decreased the risk of both HF hospitalization and mortality. These clinical trials showed that SGLT2 inhibitors have positive effects on patients with cardiovascular diseases 9,12,13. DPP4 inhibitors were determined not to be inferior, but saxagliptin was associated with significantly increased rate of HF hospitalization 10…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These benefits lead to cardiovascular protection through decreasing weight, lowering blood pressure, increasing the elasticity of the arteries and reducing its stiffness, lowering lipid production, decreasing systemic inflammation and the release of inflammatory biomarkers, increasing insulin production, decreasing insulin resistance, and decreasing uric acid levels. 16,17 Among studies reporting these benefits was a study conducted on apolipoprotein Eedeficient mice. These mice were fed a Western diet for 20 weeks and were treated with empagliflozin for 8 weeks.…”
Section: Sglt2 Inhibitorsmentioning
confidence: 99%